KARAKTERISTIK FISIKA DAN KIMIA PROFIL TANAH DASAR KOLAM DI DESA KOTO MESJID KABUPATEN KAMPAR - Hasibuan, Saberina; Syafriadiman, Syafriadiman (Fakultas Perikanan dan Kelautan Universitas Riau, 2013)
The research was conducted from April until June 2012 at Soil and Water Quali-ty Management Laboratory Fisheries and Marine Science Faculty of Riau University.The aim of the research was to know chemical and physical characteristics of pondbottom soil and profiles of PMK soil as potencial to development fish pond. The meth-od used was experimental and make up profiles in four lokation.Characteristics of fish pond bottom soil showed relatively acidic soil (PodsolidRed Yellow) with pH ranging from 4.9 to 5.7, the medium to hight levels of organicmatter (1.56 to 2.21%) and low of total N and CEC. Some locations are potentialenough to build a fish pond, although still need to achive pond bottom soil primarilyuse agricultural lime and organic matter to increase of on CEC and the productivity offish pond.